2011
DOI: 10.1371/journal.pone.0018184
|View full text |Cite
|
Sign up to set email alerts
|

The Pseudomonas aeruginosa Chemotaxis Methyltransferase CheR1 Impacts on Bacterial Surface Sampling

Abstract: The characterization of factors contributing to the formation and development of surface-associated bacterial communities known as biofilms has become an area of intense interest since biofilms have a major impact on human health, the environment and industry. Various studies have demonstrated that motility, including swimming, swarming and twitching, seems to play an important role in the surface colonization and establishment of structured biofilms. Thereby, the impact of chemotaxis on biofilm formation has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 62 publications
4
50
0
Order By: Relevance
“…In vitro methylation assays using membranes prepared from E. coli cells that express PctA and purified CheR1 from P. aeruginosa have demonstrated that PctA is methylated by CheR1 methyltransferase at a rate that is increased by attractant stimuli (Schmidt et al, 2011). However, those authors did not determine the sites at which the methylation occurred.…”
Section: Discussion Pctapp Signalling Abilities Within E Coli Complexesmentioning
confidence: 99%
“…In vitro methylation assays using membranes prepared from E. coli cells that express PctA and purified CheR1 from P. aeruginosa have demonstrated that PctA is methylated by CheR1 methyltransferase at a rate that is increased by attractant stimuli (Schmidt et al, 2011). However, those authors did not determine the sites at which the methylation occurred.…”
Section: Discussion Pctapp Signalling Abilities Within E Coli Complexesmentioning
confidence: 99%
“…The diameter of bacterial colonies and the clear-zone diameter were measured with calipers (Schmidt et al, 2011).…”
Section: Measurement Of Colony Diameter and Diameter Of Clear Zonementioning
confidence: 99%
“…Chemotaxis is required for outward migration of the swarming colony in V. parahaemolyticus and Vibrio alginolyticus (80,81), but not for any of the other bacteria examined to date. In Rhodospirillum centenum, B. subtilis, and P. aeruginosa, nonchemotactic mutants whose flagellar motors are CCW biased (expected to form flagellar bundles) can swarm, while those that are CW biased do not (82)(83)(84). Aberrant and nonswarming patterns have been reported for nonchemotactic mutants of P. mirabilis (85), but chemotaxis is apparently not required for swarming (86).…”
Section: Signaling Pathways That Control the Decision To Movementioning
confidence: 99%